Odpowiedzi

2009-06-04T09:27:53+02:00
A=7 b=9 c=11

a+b+c=27
2b=a+c
(b+3)2 =(a+1)(c+7) ( te 2 za nawiasem oznacza do kwadratu)

czyli

a=17
b=9
c=1


  • Użytkownik Zadane
2009-06-04T09:37:27+02:00
C .arytmetyczny
a₁=a
a₂=a+r
a₃=a+2r

S₃=27
S₃=a+a+r+a+2r
27=3a+3r
9=a+r a=9-r

c.geometryczny
b₁=a+1
b₂=a+r+3
b₃=a+2r+7

za a podstawiamy 9-r
b₁=9-r+1=10-r
b₂=9-r+r+3=12
b₃=9-r+2r+7=16+r

z c.goemetrycznego mamy zależność
b₂:b₁=b₃:b₂
12:(10-r)=(16+r):12
12*12=(10-r)(16+r)
144=160+10r-16r-r²
r²+6r-16=0
Δ=6²-4*1*(-16)=36+64=100
√Δ=10
r₁=(-6+10):2=2
r₂=(-6-10):2=-8

dla r=2
a=9-2=7

a₁=7
a₂=9
a₃=11


dla r=-8
a=9-(-8)=17

a₁=17
a₂=9
a₃=1